Spark plasma sintering preparation of reference targets for field spectroscopy on Mars. (21st June 2018) - Montagnac, G.; Dromart, G.; Beck, P.; Mercier, F.; Reynard, B.; Cousin, A.; Maurice, S.; Wiens, R.
Abstract: We propose spark plasma sintering (SPS) as a technique to prepare reference targets for Raman and other spectroscopy instruments involved in future space missions and more generally in‐field work. We have tested the effect of SPS on different international standards that are available in the form of minerals and rocks powders. Advantages and potential issues of SPS were considered by analyzing the Raman signal and mechanical properties of the sintered targets. The shape is well controlled; the rupture toughness is enhanced, and the homogeneous distribution of the mineral phases is verified. A suite of calibration targets has thus been implemented for the SuperCam instrument on the National Aeronautics and Space Administration Mars 2020 rover, and SPS may be preferred for future missions as well. Abstract : We propose spark plasma sintering (SPS) as a technique to prepare reference targets for Raman and other spectroscopy instruments involved in future space missions and more generally in‐field work. A suite of calibration targets has thus been implemented for the SuperCam instrument on the NASA Mars 2020 rover, and SPS may be preferred for future missions as well.